Out-of-order parallel simulation for ESL design - Chen, Weiwei; Han, Xu; Dömer, Rainer (Proceedings of the Conference on Design, Automation and Test in Europe, 2012)
At the Electronic System Level (ESL), design validation often relies on discrete event (DE) simulation. Recently, parallel simulators have been proposed which increase simulation speed by using multiple cores available on today's PCs. However, the total order of time in DE simulation is a bottleneck that severely limits the benefits of parallel simulation. This paper presents a new out-of-order simulator for multi-core parallel DE simulation of hardware/software designs at any abstraction level. By localizing the simulation time and carefully handling events at different times, a system model can be simulated following a partial order of time. Subject to automatic static data analysis at compile time and table-based decisions at run time, threads can be issued early which reduces the idle time of available cores. Our experiments show high performance gains in simulation speed with only a small increase of compile time.